2003
DOI: 10.1159/000078162
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Genetic Testing for Increased Cancer Risk in the Year 2000 National Health Interview Survey

Abstract: Objectives: This study explores factors associated with differential awareness of genetic tests for increased cancer risk in the US. Methods: 27,405 respondents from the 2000 National Health Interview Survey, ages 25+, were asked if they had heard of these tests. Results: 44.4% said ‘yes’, including 49.9% of whites, 32.9% of African-Americans, 32.3% of American Indians/Alaskan Natives, 28.0% of Asian/Pacific Islanders, and 20.6% of Hispanics. In multivariate analysis, test awareness was significantly associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 39 publications
3
68
1
Order By: Relevance
“…[19][20][21][22][23] This may be explained in part by factors such as education, acculturation, and region of residence, although differences remain apparent even after adjustment for many sociodemographic factors. 21 To our knowledge, however, this is the first study to report that Hispanics and African Americans who are aware of genetic testing are more likely to discuss it with their physicians or to undergo testing when advised by their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23] This may be explained in part by factors such as education, acculturation, and region of residence, although differences remain apparent even after adjustment for many sociodemographic factors. 21 To our knowledge, however, this is the first study to report that Hispanics and African Americans who are aware of genetic testing are more likely to discuss it with their physicians or to undergo testing when advised by their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect women's minimal knowledge about GT. Data from both the 2000 and 2005 National Health Interview Survey suggested that less than one third of Puerto Rican women have heard of GT for inherited cancer susceptibility, compared to approximately half of all Whites (Heck et al 2008;Vadaparampil et al 2006;Wideroff et al 2003). A recent analysis of qualitative data from the larger study based in Tampa further supports this lack of familiarity with cancer-related GT as participants from various Hispanic ethnicities, including Puerto Rico, would not know how to describe GT to a friend (Vadaparampil et al 2010a).…”
Section: Knowledge About Hereditary Cancer By Locationmentioning
confidence: 99%
“…However, this awareness varies by socio-demographics, family history, access to information through the health care system (Meischke et al, 2001;Benjamin-Garner et al, 2002;Wideroff et al, 2003;Vadaparampil et al, 2006) and the perceived personal risk (Bottorff et al, 2002;Bruno et al, 2004). Also, individual's decision regarding whether or not to seek clinical cancer genetic services may also be influenced by knowledge, cognitions, emotions, family communication, and socio-demographic and clinical characteristics (Bottorff, 2002;Kinney et al 2006;Ropk et al, 2006).…”
Section: Introductionmentioning
confidence: 99%